Soft Compactness and Soft Topological Separate axioms - Fu, Li; Fu, Hua (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
In this paper, we further discuss soft compactness and soft separation axioms in the soft topological space over the roughÂ soft formal context T = (G;M;R; F). We define the compact soft topological space , give soft separation axioms of soft roughÂ topological space and study their relationship in the soft topological space over the rough soft formal context.